Laura Anderson Barbata - singing leaf September 9 - October 28, 2023, Marlborough Gallery, 545 West 25th Street, New York, NY 10001 - Sullivan, Edward J. 1949-; Turner, Madeline Murphy (Marlborough, 2023)
Singing Leaf is the first solo exhibition at the Marlborough Gallery of the transdisciplinary artist Laura Anderson Barbata (b. Mexico, immigrated to the USA). Occupying two floors of the exhibition highlights nearly three decades of the artists rich and varied output across time and place. Works on view include photography, drawings, collages, textiles, video, installation, and sculpture, as well as mixed-media documentation from a selection of social projects initiated with numerous collaborators. Since the early-1990s, Laura Anderson Barbara has initiated art-centered projects in the United States, the Venezuelan Amazon, Trinidad and Tobago, Mexico, and Norway which emphasize reciprocity, shared knowledge, and decolonial thinking. Through anchoring objects, Singing Leaf gathers many traditions, voices, and communities that are empowered by the artists expansive definitions of authorship and collaboration. The exhibition includes a selection of works on paper (reminiscent of the type of the Mexican "papel picado") and zines that respond to and reflect upon the artist's project "The Repatriation of Julia Pastranaʺ. Started in 2005, the anthropological and humanitarian project traces the 2013 removal and repatriation to her homeland of Sinaloa, Mexico of the body of Julia Pastrana (Sinaloa 1834-1860), a 19th century woman exhibited in life and after death as The Ugliest Woman in the World,ʺ from a storage facility in Oslos Schreiner Collection. Unlike her other collaborations, the artist herself does not consider The Repatriation of Julia Pastranaʺ a work of art. This was an additive projects -or parts of the creative impulse that drove [the artist] to embark on her decade-long quest. They document and commemorate the events, yet they are subordinate to the essential altruistic and deeply political implications of the action itself.ʺ
Keywords: Anderson Barbata, Laura -- 1958-; Ausstellungskatalog -- Marlborough Gallery -- 09.09.2023-28.10.2023 -- New York, NY; Bildband